The XPF-ERCC1 endonuclease and homologous recombination contribute to the repair of minor groove DNA interstrand crosslinks in mammalian cells produced by the pyrrolo[2,1-c][1,4]benzodiazepine dimer SJG-136 - Clingen, Peter H. (Oxford University Press, 2005)
SJG-136, a pyrrolo[2,1-c][1,4]benzodiazepine (PBD) dimer, is a highly efficient interstrand crosslinking agent that reacts with guanine bases in a 5′-GATC-3′ sequence in the DNA minor groove. SJG-136 crosslinks form rapidly and persist compared to those produced by conventional crosslinking agents such as nitrogen mustard, melphalan or cisplatin which bind in the DNA major groove. A panel of Chinese hamster ovary (CHO) cells with defined defects in specific DNA repair pathways were exposed to the bi-functional agents SJG-136 and melphalan, and to their mono-functional analogues mmy-SJG and mono-functional melphalan. SJG-136 was >100 times more cytotoxic than melphalan, and the bi-functional agents were much more cytotoxic than their respective mono-functional analogues. Cellular sensitivity of both SJG-136 and melphalan was dependent on the XPF-ERCC1 heterodimer, and homologous recombination repair factors XRCC2 and XRCC3. The relative level of sensitivity of these repair mutant cell lines to SJG-136 was, however, significantly less than with major groove crosslinking agents. In contrast to melphalan, there was no clear correlation between sensitivity to SJG-136 and crosslink unhooking capacity measured using a modified comet assay. Furthermore, repair of SJG-136 crosslinks did not involve the formation of DNA double-strand breaks. SJG-136 cytotoxicity is likely to result from the poor recognition of DNA damage by repair proteins resulting in the slow repair of both mono-adducts and more importantly crosslinks in the minor groove.